German philosophy, 1760-1860 : the legacy of idealism - Pinkard, Terry P. (2002)
In the second half of the eighteenth century, German philosophy came for a while to dominate European philosophy. It changed the way in which not only Europeans, but people all over the world, conceived of themselves and thought about nature, religion, human history, politics, and the structure of the human mind. In this wide-ranging book, Terry Pinkard interweaves the story of 'Germany' - changing during this period from a loose collection of principalities into a newly-emerged nation with a distinctive culture-with an examination of the currents and complexities of its developing philosophical thought. He examines the dominant influence of Kant, with his revolutionary emphasis on 'self-determination', and traces this influence through the development of romanticism and idealism to the critiques of post-Kantian thinkers such as Schopenhauer and Kierkegaard. His book will interest a range of readers in the history of philosophy, cultural history and the history of ideas